Efektivitas Pembelajaran Daring Pada Masa Covid di SMAN 2 Salatiga - Irna Eltri Samoling; Bambang Ismanto; Lelahester Rina (Scholaria: Jurnal Pendidikan dan Kebudayaan, 2022)
E-learning is a learning that USES technology and can be done anywhere at any time. The purpose of this study is to describe the effectiveness of the application of online learning during the covid pandemic at sman 2 salatiga. The research approach used in this study is a qualitative approach. This type of research is a descriptive analysis model that describes the problem. The data-collection technique that researchers use is observation, the kind of observation used in this study is passive participation. Passive participative observations are made by observation but do not participate in these activities. Interviews, the kind of interviews used were structured interviews. Documentation is used to study data that has been collected. The results of this study indicate that the online learning program at SMAN 2 Salatiga has been effective from a cognitive perspective, but from an affective and psychomotor perspective it has not been effective. Because learning is not just providing material and assignments, but how educators teach factually, inquiry of all material. So, with the CIPP evaluation on online learning, the school can evaluate each policy that is determined (feasibility).